Today's state of the art in surgical robotics - Pott, Peter Paul; Scharf, Hanns-Peter; Schwarz, Markus (Computer aided surgery, 2010)
Objective: This paper describes the current level of development of robots for surgery.Material and Methods: This paper is based on a literature search in Pubmed, IEEExplore, CiteSeer and the abstract volumes of the MICCAI 2002, 2003 and 2004, CARS 2003 and 2004, CAOS 2003 and 2004, CURAC 2003 and 2004 and MRNV 2004 meetings.Results: Divided into different disciplines (imaging, abdominal and thoracic surgery, ENT, OMS, neurosurgery, orthopaedic surgery, radiosurgery, trauma surgery, urology), 159 robot systems are introduced. Their functionality, deployment, origin and mechanical set-up are described. Additional contacts and internet links are listed.Conclusions: The systems perform diverse tasks such as milling cavities in bone, harvesting skin, screwing pedicles or irradiating tumors. From a technical perspective the strong specialization of the systems stands out. Most of the systems are being developed in Germany, the United States, Japan or France.